The Effect of Cue Card Media Towards Students’ Vocabulary Mastery at The Eight Grade of SMP IT Daarul Uzma Picung in Academic Years 2023/2024 - Esih Novia; Ade Sudirman; Ari Fajria Novari (Journal on Education, 2024)
The purpose of this study was to determine, first whether or not there is a significant effect on the vocabulary mastery of eighth grade A students taught using cue card media at SMP IT Daarul Uzma, before and after treatment and second whether or not there is a significant difference in the vocabulary mastery of eighth grade B students taught using flashcard media. The population of this study was 42 students. The sample of this study was 42 eighth grade students of SMP IT Daarul Uzma Picung, which were divided into experimental and control groups, and each group consisted of 21 students. The sample selection technique was done by purposive sampling. To collect data, each group was given a pre-test and post-test. The data analysis technique used in this research is paired sample ttest which is calculated using SPSS 26. Based on the results of data analysis, the average results of the post-test of the experimental class and the control class are different, namely 77.43 and 69.52 and for the results of the t-test obtained a significance value of 0.000 ≤ α = 0.05. These results show that the alternative hypothesis (Ha) is accepted and the null hypothesis (H0) is rejected. Thus, there is a significant effect on vocabulary mastery by using cue card media.